Methods of measurement of LTCC metallization thickness - Khiang, Lee Soo; Norhawati, Ahmad; Muammar, Mohamad Isa; Rosidah, Alias (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/